The impact of renewable energy diffusion on European consumption-based emissions. Issue 2 (2nd April 2016) - Wiebe, Kirsten S.
ABSTRACT: The amount of carbon embedded in the final consumption of goods and services in a country or region depends on the amount of goods and services consumed and the emission intensity of the production processes along global production chains. A reduction of consumption-based emissions can be achieved from both sides, a reduction in total consumption and a reduction in the emission intensity of the production processes. The power sector is one of the most carbon intensive industries along global production chains and the global deployment of renewable power generation technologies (RPGTs) is one possibility to significantly reduce emissions in this industry. This paper combines three different strands of literature, multi-regional input–output analysis, dynamic energy–economy–environment models and technological change in renewable energy (RE), to model the impact of the global diffusion of renewable energies on European consumption-based emissions. The global diffusion of RE technologies (photovoltaic and wind) depends on the development of technology costs, which are modeled using learning curves. With increasing deployment of renewables within the EU as well as increasing RD&D efforts, the EU can achieve an accelerated costs decrease for these technologies, thus fostering deployment of RPGTs at a global scale through the effect of decreasing costs. This behavior indirectly influences the electricity mix abroad, making it less carbon intensive, so that consumption-based emissions of the EU decrease.